Reconectando igualdad: bases teóricas para la exploración de una posible implementación de los videojuegos en nuevas estrategias de alfabetización digital - González, Teresa (2013)
Reconnecting Equality Project is for training high school students in new technologies for creative and genuine ownership of netbooks provided by Connect-Equality Plan. The project aims to promote students´s social inclusion in the Information Society and provide them the skills to design and use computers as productivity tools. This will be possible through an extracurricular workshop of design and video games development. We are an interdisciplinary team, belonging to the areas of sociology, business, social work, graphic design, multimedia design, pedagogy and social communication.